World myths and legends : 25 projects you can build yourself - Ceceri, Kathy; Braley, Shawn (White River Junction, VT : Nomad Press, 2010)
Provides a look at the origins of myths and legends, summarizes the characters and stories used to explain the natural world and human behavior, and includes hands-on activities, fun facts, and modern-day connections.
What are myths and legends? -- The Middle East -- Greece and Rome -- Northern Europe -- Sub-Sahara Africa -- India and China -- Japan and Australia -- Central and South America -- North America.
Includes index.
Includes bibliographical references (page 116) and index.
950
Keywords: Mythology; Heroes -- Mythology; Folklore; Handicraft; Juvenile literature